2020
DOI: 10.1111/1751-7915.13619
|View full text |Cite
|
Sign up to set email alerts
|

The urgent need for microbiology literacy in society: children as educators

Abstract: Summary Microbes and their activities have pervasive influence and deterministic roles in the functioning and health of the geosphere, atmosphere and biosphere, i.e. in nature. Microbiology can be considered a language of nature . We have argued that the relevance of microbes for everyday personal decisions and collective policies requires that society attains microbiology literacy, through the introduction of child‐relevant microbiology topics into school curricula. That is: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 6 publications
0
23
0
2
Order By: Relevance
“…As also can be seen from the Strike for Climate movement, they enjoy interacting with others, especially via social media, and participating in international activities, interactions that can amplify their enthusiasm and motivation. To engage and stimulate this enthusiasm for group activities, the IMiLI is developing family-friendly network projects and international citizen science projects ( 15 ).…”
Section: Editorialmentioning
confidence: 99%
See 1 more Smart Citation
“…As also can be seen from the Strike for Climate movement, they enjoy interacting with others, especially via social media, and participating in international activities, interactions that can amplify their enthusiasm and motivation. To engage and stimulate this enthusiasm for group activities, the IMiLI is developing family-friendly network projects and international citizen science projects ( 15 ).…”
Section: Editorialmentioning
confidence: 99%
“…Another aspect of empowerment of children is their ability to act themselves as educators ( 15 ), as agents of knowledge transmission among family members and friends and peer networks. The pupil or student centricity of the curriculum, the portrait galleries that expose fascinating personalities of microbes, and the family projects being designed will all stimulate the natural tendency of children to transmit their newly acquired microbiology knowledge and feeling of empowerment.…”
Section: Editorialmentioning
confidence: 99%
“…Microorganismo es un término científico que incluye grupos taxonómicos muy diferentes: protozoarios, hongos, bacterias, arqueas, algas y virus. Más allá de la controversia de si los virus son o no son seres vivos, en general, son considerados microorganismos (Timmis et al, 2019;Simard, 2021). El conocimiento de esta terminología más precisa y su significado constituyen un primer paso en el proceso de alfabetización científica en este ámbito que supera la denominación de germen, más imprecisa y ligada a la enfermedad, empleada en estudios más antiguos (Nagy, 1953;Kalish, 1996;Jones y Rua, 2006).…”
Section: Importancia De La Educación En Microbiologíaunclassified
“…Recientemente, desde las sociedades científicas internacionales, se ha reclamado su inclusión en los currículos escolares desde educación infantil hasta la educación secundaria, dada la relevancia social de los conocimientos sobre microbiología tanto en el ámbito sanitario, para un uso adecuado de los antibióticos y ante el grave peligro de la no vacunación, como por su prevalencia y relevancia en los ecosistemas y en muchos procesos industriales(Timmis et al, 2019). Es la primera cuestión, la higiénico-sanitaria, la que más iniciativas previas ha tenido en la generación de materiales escolares.…”
unclassified
“…Through the program, the children's awareness of climate change increased, and they subsequently shared their newly acquired knowledge with their families and communities. Timmis et al (2020) also demonstrated the importance of children in the communication of science within families. More specifically, they found that children can impact parental decisions and work against misinformation in their families.…”
mentioning
confidence: 93%